RELIABILITY ANALYSIS OF MECHANISM OVER-CENTER LOCKING CONSIDERING WEAR AND CLEARANCE - QIN Qiang; LI TingTing; FENG YunWen; XUE XiaoFeng (Jixie qiangdu)
Depending on the form of mechanism,the hinge wear and rod end bearing wear are considered respectively,and the self-lubricating rod end bearing wear model are established.Then the over-center locking reliability analysis model of four bar linkage mechanism is built under the "effective lever length theory"and "continuous contact model"hypothesis,besides,a reliability analysis method of over-center locking considering the initial clearance and wear is presented.The results show that the failure probability of mechanism over-center locking will rapidly increase after a certain number of cycles; the reliability of mechanism over-center locking will be significantly improved by using self-lubricating rod end spherical plain bearing.